Advantages of the retroperitoneal retrocolic space as the transplant site for encapsulated xenogeneic islets. (1st December 2022) - Geng, Zhen; Zhang, Qi; Li, Ting; Huang, Ting; Wang, Hailian; Zhou, Qiao; Deng, Shaoping; Zhao, Yanshuang; Li, Yanjiao; Cheng, Chunming; Gonelle‐Gispert, Carmen; Buhler, Leo H.; et al.
Abstract: Objective: Islet allotransplantation has demonstrated improved clinical outcomes using the hepatic portal vein as the standard infusion method. However, the current implantation site is not ideal due to the short‐term thrombotic and long‐term immune destruction. Meanwhile, the shortage of human organ donors further limits its application. To find a new strategy, we tested a new polymer combination for islet encapsulation and transplantation. Meanwhile, we explored a new site for xenogeneic islet transplantation in mice. Method: We synthesized a hydrogel combining alginate plus poly‐ethylene‐imine (Alg/PEI) for the encapsulation of rat, neonatal porcine, and human islets. Transplantation was performed into the retroperitoneal retro‐colic space of diabetic mice. Control mice received free islets under the kidney capsule or encapsulated islets into the peritoneum. The biochemical indexes were measured, and the transplanted islets were harvested for immunohistochemical staining of insulin and glucagon. Results: Mice receiving encapsulated rat, porcine and human islets transplanted into the retroperitoneal space maintained normoglycemia for a median of 275, 145.5, and 146 days, respectively. In contrast, encapsulated xenogeneic islets transplanted into the peritoneum, maintained function for a median of 61, 95.5, and 82 days, respectively. Meanwhile, xenogeneic islets transplanted free into the kidney capsule lost their function within 3 days after transplantation. Immunohistochemical staining of encapsulated rat, porcine and human islets, retrieved from the retroperitoneal space, allowed to distinguish morphological normal insulin expressing β‐ and glucagon expressing α‐cells at 70, 60, and 100 days post‐transplant, respectively. Conclusion: Transplantation of Alg/PEI encapsulated xenogeneic islets into the retroperitoneal space provides a valuable new implantation strategy for the treatment of type 1 diabetes.